2016
DOI: 10.1186/s12940-016-0176-2
|View full text |Cite
|
Sign up to set email alerts
|

Association between phthalate exposure and lower handgrip strength in an elderly population: a repeated-measures study

Abstract: BackgroundDecreased muscle strength can lead to adverse health outcomes in the elderly. A potential association between phthalate exposure and muscle strength was suggested previously, but has not been investigated directly. We hypothesized that phthalate exposure is associated with lower handgrip strength and that the association is modified by the dietary omega-6 to omega-3 ratio.MethodsWe analyzed 1,228 participants (≥60 years of age) recruited in Seoul and Asan, Republic of Korea. The study participants we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Two primary exposure variables were used in this study: handgrip strength and BMI from the first wave. Handgrip strength was measured by using a dynamometer (Model number: NO6103, Manufacturer: TANITA, Japan), which measures handgrip strength in units of 0.1 kgF and has been used in multiple previous studies that determined handgrip strength [ 18 , 19 ]. Upon measurement, the participant was in a seated or standing position, her elbow at a right angle, and the wrist in neutral position.…”
Section: Methodsmentioning
confidence: 99%
“…Two primary exposure variables were used in this study: handgrip strength and BMI from the first wave. Handgrip strength was measured by using a dynamometer (Model number: NO6103, Manufacturer: TANITA, Japan), which measures handgrip strength in units of 0.1 kgF and has been used in multiple previous studies that determined handgrip strength [ 18 , 19 ]. Upon measurement, the participant was in a seated or standing position, her elbow at a right angle, and the wrist in neutral position.…”
Section: Methodsmentioning
confidence: 99%
“…The team conducted physical and functional assessments (e.g., anthropometric measurement, handgrip strength, walking speed) and collected and analyzed urine and blood specimens. The details of the KEEP II study have been reported elsewhere [ 20 , 21 ]. The Institutional Review Board at Seoul National University Hospital approved the study protocol (C-1209-006-424).…”
Section: Methodsmentioning
confidence: 99%
“…Socio-demographic data included age, gender, education, household type, house income, occupation, and living location [ 3 , 5 , 6 , 9 , 10 , 11 , 12 , 19 , 20 , 21 ]. Lifestyle data included smoking, drinking, and fruit and vegetable consumption [ 6 , 10 , 12 , 19 , 20 , 21 , 25 ]. “Non-smoker” refers to a person who reported smoking fewer than 20 packs of cigarettes during their lifetime, and “non-drinker” refers to a person who reported (s)he could not or did not drink alcohol (e.g., due to religion).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While little is known about the effects of MEHP on human skeletal muscle, a decrease in muscle strength in the elderly has been shown to be parallel with increasing urinary MEHP, which was hypothesized to be a result of MEHP-induced oxidative stress and inflammation (24). Furthermore, Corbasson et al (2016) illustrated an association between increased urinary MEHP and decreased lean mass in adults, where lean mass excluded bone mineral content, thus primarily representing muscle mass (25).…”
Section: Introductionmentioning
confidence: 99%